Legality of Share Ownership Based on Nominee Agreements in Indonesian Law - Ronaldi Agustinus; Diki Zukriadi (Sean Institute, 2025)
This study aims to examine the legal implications and validity of nominee arrangements in the ownership structure of limited liability companies in Indonesia, particularly in the context of restrictions on foreign investment. The research seeks to analyze the alignment between the practice of nominee shareholding and the principles of legality, justice, and legal certainty as upheld in Indonesian corporate and investment law. Employing a normative juridical approach, the study focuses on written legal norms, statutory regulations, and doctrinal analysis within the national legal system. The research data were obtained from secondary legal materials, including legislation, judicial decisions, scholarly writings, and relevant literature collected through systematic document review and library research. Data were analyzed using deductive reasoning and a descriptive-analytical technique to assess the coherence and consistency among the applicable legal norms. The findings reveal that nominee practices, although often justified under the principle of contractual freedom, in substance contradict the legal prohibition on indirect foreign ownership as stipulated in investment law. Such arrangements undermine the doctrine of good faith, distort the principle of limited liability, and create ambiguity in shareholder accountability. Consequently, nominee agreements are deemed legally flawed and contrary to public order because their intent conceals actual ownership and circumvents statutory limitations. The study concludes that reformulating corporate and investment regulations is essential to ensure transparency, uphold justice, and reinforce the rule of law in Indonesia’s investment environment.